Preoperative Vitamin D Concentration and Cardiac, Renal, and Infectious Morbidity after Noncardiac Surgery. (January 2020) - Turan, Alparslan; Artis, Amanda S.; Hanline, Cecelia; Saha, Partha; Maheshwari, Kamal; Kurz, Andrea; Devereaux, P. J.; Duceppe, Emmanuelle; Patel, Ameen; Tiboni, Maria; Ruetzler, Kurt; Pearse, Rupert; et al.
Abstract : Background: Low 25-hydroxyvitamin D is associated with cardiovascular, renal, and infectious risks. Postsurgical patients are susceptible to similar complications, but whether vitamin D deficiency contributes to postoperative complications remains unclear. We tested whether low preoperative vitamin D is associated with cardiovascular events within 30 days after noncardiac surgery. Methods: We evaluated a subset of patients enrolled in the biobank substudy of the Vascular events In noncardiac Surgery patIents cOhort evaluatioN (VISION) study, who were at least 45 yr with at least an overnight hospitalization. Blood was collected preoperatively, and 25-hydroxyvitamin D was measured in stored samples. The primary outcome was the composite of cardiovascular events (death, myocardial injury, nonfatal cardiac arrest, stroke, congestive heart failure) within 30 postoperative days. Secondary outcomes were kidney injury and infectious complications. Results: A total of 3, 851 participants were eligible for analysis. Preoperative 25-hydroxyvitamin D concentration was 70 ± 30 nmol/l, and 62% of patients were vitamin D deficient. Overall, 26 (0.7%) patients died, 41 (1.1%) had congestive heart failure or nonfatal cardiac arrest, 540 (14%) had myocardial injury, and 15 (0.4%) had strokes. Preoperative vitamin D concentration was not associated with the primary outcome (average relative effect odds ratio [95% CI]: 0.93 [0.85, 1.01] per 10 nmol/l increase in preoperative vitamin D, P = 0.095). However, it was associated with postoperative infection (average relative effect odds ratio [95% CI]: 0.94 [0.90, 0.98] per 10 nmol/l increase in preoperative vitamin D, P adjusted value = 0.005) and kidney function (estimated mean change in postoperative estimated glomerular filtration rate [95% CI]: 0.29 [0.11, 0.48] ml min -1 1.73 m -2 per 10 nmol/l increase in preoperative vitamin D, P adjusted value = 0.004). Conclusions: Preoperative vitamin D was not associated with a composite of postoperative 30-day cardiac outcomes. However, there was a significant association between vitamin D deficiency and a composite of infectious complications and decreased kidney function. While renal effects were not clinically meaningful, the effect of vitamin D supplementation on infectious complications requires further study. Abstract : Vitamin D deficiency was common in this surgical population. Preoperative vitamin D was not associated with a composite of postoperative 30-day cardiac outcomes. There was an association between low vitamin D and a composite of infectious complications, and also evidence for an association with decreased kidney function.Supplemental Digital Content is available in the text.